Low band‐gap diketopyrrolopyrrole‐containing polymers for near infrared electrochromic and photovoltaic applications. Issue 10 (3rd March 2015) - Low, Jonathan Zhaozhi; Neo, Wei Teng; Ye, Qun; Ong, Wen Jie; Wong, Ivy Hoi Ka; Lin, Ting Ting; Xu, Jianwei
ABSTRACT Donor–acceptor type polymers bearing diketopyrrolopyrrole and 3, 4‐ethylenedioxythiophene units are reported. The polymers are green and exhibit very low band‐gaps (1.19 eV) with strong and broad absorption (maxima of about 830 nm) in the near infrared (NIR) region in their neutral film states. The polymers display color changes between dark green and light blue with exceptional optical contrasts in the NIR regions of up to 78 and 63% as thin films and single‐layer electrochromic devices, respectively. Fast switching, good stabilities as well as high coloration efficiencies (743–901 cm2 C−1) were also observed. The polymers could also be potentially used as photovoltaic material, with a power conversion efficiency of up to 1.68%. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 1287–1295